THE ROLE OF CORE COMPETENCIES ON ORGANIZATIONAL PERFORMANCE: AN EMPIRICAL STUDY IN THE IRAQI PRIVATE BANKING SECTOR - Jabbouri, Nada Ismaeel; Zahari, Ibrahim (European Scientific Journal, ESJ, 2014)
This paper discusses the impact of core competences on organizational performance as a critical issue in Iraqi private banking sector. An organizer questionnaire was developed and self-reported to managers in 10 private banks, a sample of this study are 200 managers in these banks. The hypothesis to test variables of the study was absorbed in a questionnaire with Cronbach’s alpha coefficient of 75% and was prepared based on a number of measures related to the subject of study. A range of methods were used to analyses statistical data, and the results were extracted using SPSS. The result shows that there is a significant correlation among core competences and organizational performance. Based on this, we recommend that bank management develop of the core competences for human resource as a strategic tool to enhance organizational performance and expand their empirical knowledge in the context of private banks in Iraq.